Espying Heaven : The Stained Glass of Charles Eamer Kempe and His Artists - Barlow, Adrian (Lutterworth Press, The, 2019)
A lavishly-illustrated exploration of the work of the Victorian church artist Charles Eamer Kempe and the team of artists he led and inspired.